Managing digital transformations: the intermediary function of digital readiness in facilitating strategic renewal within the healthcare industry - Erwin Tenggono; Budi W. Soetjipto; Lily Sudhartio (Cogent Business & Management, 2024)
The study investigates the direct influence of Institutional Pressures (IP) and Dynamic Managerial Capability (DMC) on digital readiness (DR), and the subsequent impact on strategic renewal (SR) within private hospitals in Indonesia. Utilizing a quantitative approach and a cross-sectional research design, 231 valid responses were analyzed using smart partial least squares (PLS) for structural equation modeling (SEM). The findings reveal that institutional pressure directly affects digital readiness, emphasizing the critical role of DMC in mediating the relationship between institutional pressure and digital readiness. Furthermore, the study highlights the strong connection between digital readiness and strategic renewal, underscoring the organization's capability for digital transformation. The originality of this study lies in its exploration of the interplay between institutional pressures, dynamic managerial capabilities (DMC), and digital readiness (DR) in shaping strategic renewal within private hospitals in Indonesia. By examining how institutional pressures influence DR and the mediating role of DMC, this research uniquely contributes to the understanding of digital transformation challenges in healthcare, offering valuable insights for organizations seeking to enhance their strategic responses in facing digital disruptions.
Keywords: 650; Digital Readiness; Digital Transformation; Healthcare Organization; Institutional Pressures; Strategic Agility; Strategic Renewal